Characteristics of clinical isolates of nontuberculous mycobacteria in Java-Indonesia: A multicenter study. - Leli Saptawati; Widana Primaningtyas; Paramasari Dirgahayu; Yusup Subagio Sutanto; Brian Wasita; Betty Suryawati; Titik Nuryastuti; Ari Probandari (Public Library of Science (PLoS), 2022)
Background Nontuberculous mycobacterial (NTM) lung infections are a major public health concern. Diagnosis of NTM-pulmonary disease (NTM-PD) is difficult because its clinical, microbiological, and radiological features resemble to those of pulmonary tuberculosis (TB), leading to misdiagnosis. Identification at the species level is essential for diagnosis and determination of therapy, which is currently not performed routinely in Indonesian laboratories. Methodology and principal findings From January 2020 to May 2021, 94 NTM isolates were collected from three TB referral centers in Java Province. Species were identified using matrix-assisted laser desorption-ionization time-of-flight mass spectrometry (MALDI-TOF MS). Tests were performed to determine antibiotic susceptibility, biofilm formation ability, sliding motility characteristics, and the ability to adhere to and invade pneumocytes. After identifying the species of all the isolates, we found nine groups of NTMs: M. fortuitum group 51% (48/94), M. abscessus 38.3% (36/94), M. intracellulare 3.1% (3/94), M. neoaurum 2.1% (2/94), M. chelonae 1.1% (1/94), M. gordonae 1.1% (1/94), M. szulgai 1.1% (1/94), M. mucogenicum 1.1% (1/94), and M. arupense 1.1% (1/94). Amikacin was the most effective antibiotic against M. fortuitum group and M. abscessus. The M. fortuitum group was significantly better at forming biofilms than M. abscessus, but both had the same sliding motility capability. The ability of the M. fortuitum group to adhere to and invade pneumocytes was better than that of M. abscessus, with the number isolates of the M. fortuitum group capable of superior adhesion and invasion to that of M. abscessus. Conclusions/significance This study shows that M. fortuitum group and M. abscessus were the most common NTM found in Java, Indonesia. The M. fortuitum group and M. abscessus were the most susceptible to amikacin; therefore, this was the empirical treatment of choice. The ability to form biofilms is directly proportional to the ability to adhere to and invade pneumocytes but not to the susceptibility profile or sliding motility characteristics.